Experimental and analytical research on resonance phenomena of vibrating head with MRE regulating element - Miedzińska, Danuta; Gieleta, Roman; Osiński, J. (Zielona Góra: Uniwersytet Zielonogórski)
A vibratory pile hammer (VPH) is a mechanical device used to drive steel piles as well as tube piles into soil to provide foundation support for buildings or other structures. In order to increase the stability and the efficiency of the VPH work in the over-resonance frequency, a new VPH construction was developed at the Military University of Technology. The new VPH contains a system of counter-rotating eccentric weights, powered by hydraulic motors, and designed in such a way that horizontal vibrations cancel out, while vertical vibrations are transmitted into the pile.
Keywords: vibratory pile hammer; resonance; vibrations; Fourier analysis